2018
DOI: 10.31018/jans.v10i2.1769
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of pulp and paper mill effluent using low cost adsorbents: An overview

Abstract: In the present review, the suitability of adsorption process using low cost adsorbent for the treatment of pulp and paper mill effluent has been discussed. It is clear that adsorption processes are appropriate for the removal of recalcitrant compounds such as surfactants and pesticides, among others biodegradable or non-biodegradable compound present in pulp and paper mills effluents. The importance of the adsorption is to improvement of the removal of various physico-chemical (biological oxygen demand (BOD), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…There are many techniques are available for tannery wastewater treatment to remove toxicant or pollution load but adsorption is one of the promising processes for wastewater treatment. Recently, low cost materials, including rice-husk, maple sawdust, soya cake, coal ash, peat and bone char, have been investigated as adsorbents for wastewater treatment 5 . Au et al,(2018) 6 reported that saw dust was used to remove chromium from tannery effluents.…”
Section: Introductionmentioning
confidence: 99%
“…There are many techniques are available for tannery wastewater treatment to remove toxicant or pollution load but adsorption is one of the promising processes for wastewater treatment. Recently, low cost materials, including rice-husk, maple sawdust, soya cake, coal ash, peat and bone char, have been investigated as adsorbents for wastewater treatment 5 . Au et al,(2018) 6 reported that saw dust was used to remove chromium from tannery effluents.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, pharmaceuticals such as ibuprofen, metoprolol, paracetamol, and sulfamethoxazole, when released into the environment can be highly toxic to humans, animals, and aquatic life. [50,53,59] Storm sewage includes sewage overflow and road runoff from precipitation that is collected in a system of pipes or open channels and may contain nitrogen and phosphorus pollutants from fertilizers, yard, and petrochemical wastes that pollute water bodies during heavy rainfall or snowmelt. [60] The main objectives for wastewater treatment are to reduce the levels of solids, biodegradable organic matter, pathogens, and other toxic compounds in wastewater, to meet regulatory limits that are protective of both public health and the environment.…”
Section: Wastewater: Sources Composition and Effectsmentioning
confidence: 99%
“…Classification and processes involved in conventional wastewater treatment. [49,53,59] X n T x . [82,90] Experimentally, the surface termination groups present in the MXene depend entirely on the synthesis conditions (such as etchant used, etching and delamination conditions, the types of M element, post synthetic procedure, and storage) employed during synthesis.…”
Section: Synthesis and Chemistry Of Mxenesmentioning
confidence: 99%
See 2 more Smart Citations